Breakfast consumption trends among young Australian children aged up to 5 years: results from InFANT program - Park, Seon Y.; Love, Penelope; Zheng, Miaobing; Campbell, Karen J.; Lacy, Kathleen E. (Frontiers in Endocrinology, 2023)
Breakfast is considered a healthy dietary habit which can track over time from childhood to adulthood. The breakfast meal has the potential to improve daily dietary quality, particularly if it includes a range of food groups and adequate nutrient intakes. However, research on breakfast consumption trends among young Australian children aged up to 5 years is currently limited. This study assessed children’s usual breakfast food group and nutrient intakes at ages 1.5 (n = 369), 3.5 (n = 242), and 5.0 (n =240) years using three 24-hour dietary recalls from the Melbourne InFANT program. Tracking of food groups at breakfast across the three ages was assessed by Pearson correlation of energy-adjusted food intake residuals. The main food groups consumed at breakfast were grains (including wholegrains), milk/alternatives and discretionary items, with vegetables rarely consumed at any age. For the contribution to total daily intakes, breakfast contributed more than 20% (20.5%-29.1%) of daily nutrient intakes of carbohydrate, total sugars, calcium, and potassium across all age groups despite approximately 20% of total energy intake coming from breakfast. For the contribution to daily recommendations, breakfast contributed more than about a third of daily recommended intakes for some micronutrients (e.g., iron, calcium and zinc), and a large proportion (over 40%) of sodium intake. Children consumed 11.9% -15.2% of their energy at breakfast from saturated fat, which is higher than the recommended total energy contribution of saturated fat (no more than 10% from saturated fat). For tracking of most food groups and nutrients, tracking was found to be low or moderate over time. Given the contribution that breakfast can make to ensure children achieve their daily dietary intakes, early interventions for young Australian children should focus on practical strategies to increase vegetable intake while reducing sodium and saturated fat intake at breakfast.